INCREASING ADOLESCENT KNOWLEDGE ABOUT REPRODUCTIVE HEALTH THROUGH HEALTH EDUCATION IN SMAK ST. WAENAKENG FAMILY - Raden, Natalia Damaiyanti Putri; Octaviani Laput, Dionesia (LPPM Univ. Ibn Khaldun Bogor, 2022)
Adolescents face a variety of sexual and reproductive health challenges, such as unplanned pregnancies and sexually transmitted infections, including HIV infection. This condition can be prevented with access to adequate sexual and reproductive services (including counseling and preventive treatment), adolescents often lack access and lack education in this regard, so their reproductive health challenges are not handled properly and often lead to reproductive health problems. Based on the results of the SDKI survey in 2017, it shows that there are 55% of male adolescents and 1% of women smoke, 15% of male adolescents and 1% of adolescent girls use illegal drugs, 5% of male adolescents drink alcoholic beverages, and 8% of men and 1% of women who have had sexual intercourse during courtship. The method used in this service is to provide counseling on Reproductive Health. Counseling was given to 153 students of SMAK Santa Familia Waenakeng offline at the SMAK Santa Familia Waenakeng Hall. After being given counseling on Reproductive Health, there was an increase in knowledge from the participants who took part in this activity.